Politics applications in the novel ¡Viva Cristo Rey! by Silvia Galvis - Villarreal Espinosa, Leydy Yohana; Delgado Guevara, Ingrid Johanna (Rastros Rostros, 2011)
This article is based on the investigation “Political proposals in the book ¡Viva Cristo Rey! written by Silvia Galvis” of Universidad Cooperativa de Colombia, Bucaramanga, 2009, which is developed from the application of the triple mimesis of Paul Ricoeur The motivations that can be found for the production of the play in the life of the writer, such as the partisan struggle that occurred in Colombia during the first half of the twentieth century, form the first part of the job. Literary analysis of characters Alejandro Coronado (leader of the Liberal Party) and Jose Beatriz Guerrero (leader of the Conservative Party) forms the second part, and finally staging a dash of theater built for tenth grade students. It is the proposal of teaching to be implemented in a school of Bucaramanga.